2014
DOI: 10.1007/s11033-014-3041-9
|View full text |Cite
|
Sign up to set email alerts
|

mtDNA ancestry of Rio de Janeiro population, Brazil

Abstract: Polymorphism studies concerning HVI and HVII regions of mitochondrial DNA (mtDNA) have improved the understanding of the admixture genetic process related to the occupation of the continents by human population groups. We have analyzed the mtDNA lineages of 190 healthy and maternally unrelated individuals born in the metropolitan region of the Rio de Janeiro city, the capital of the State of Rio de Janeiro, southeastern Brazil. The data showing that 57.9, 25.3 and 16.8 % of the matrilineages found in Rio de Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
3
2
0
Order By: Relevance
“…Most studies concentrating on Brazilian mitochondrial lines are limited to HV-I or HV-II sequence analysis, and therefore a more exhaustive analysis of results obtained in this study cannot be performed, especially concerning comparative evaluation of low-level mtDNA clades. However, the approximate frequencies of coarse haplogroup distribution mirrors previously reported results, with major AFR and NA contributions [25,28,[48][49][50][51][52][53][54][55]. Supplementary Figure S4 features a complete phylogenetic tree including all samples and variants observed in the present study.…”
Section: Genetic Diversity and Mtdna Haplogroup Distribution In A Bra...supporting
confidence: 88%
See 2 more Smart Citations
“…Most studies concentrating on Brazilian mitochondrial lines are limited to HV-I or HV-II sequence analysis, and therefore a more exhaustive analysis of results obtained in this study cannot be performed, especially concerning comparative evaluation of low-level mtDNA clades. However, the approximate frequencies of coarse haplogroup distribution mirrors previously reported results, with major AFR and NA contributions [25,28,[48][49][50][51][52][53][54][55]. Supplementary Figure S4 features a complete phylogenetic tree including all samples and variants observed in the present study.…”
Section: Genetic Diversity and Mtdna Haplogroup Distribution In A Bra...supporting
confidence: 88%
“…EUR populations are located at the treetop, featuring the largest distance to the Brazilian sample set. It is important to highlight that these findings are supported by previously reported genetic, historical or ethnographic information, especially for the Brazilian case [18][19][20][21][22][23][24][25][48][49][50][51][52][53][54][55].…”
Section: Inter-population Analysis Based On Mtdna Haplotype Frequenciessupporting
confidence: 80%
See 1 more Smart Citation
“…Latinos showed substantial variability in European and, to a lesser extent, Native American ancestry (except within Puerto Ricans) among and within each population, while African ancestry presented moderate to negligible variability in all populations, except for Brazilians ( Supplementary Table 2 ). Of note, the mean and variance of markers outside the autosomes may diverge from the genomic landscape depicted here ( Risch et al 2009 ; Bryc et al 2010 ; McHugh et al 2016 ; Kehdy et al 2015 ), and genealogies of uniparental markers were shown to display genetic heterogeneity ( Alves-Silva et al 2000 ; Carvalho-Silva et al 2001 ; Pena et al 2009 ; Bernardo et al 2014 ).…”
Section: Discussionmentioning
confidence: 81%
“…With its significantly higher mutation rate, mtDNA has been used as a powerful tool to trace the lineage. Methods have been developed to trace the ancestry of many species over hundreds of generations and have become a mainstay of phylogenetic and evolutionary biology (Bernardo et al, 2014). mtDNA is a circular DNA molecule that exists in multiple copies in each mitochondrion.…”
Section: Introductionmentioning
confidence: 99%